THE SURGICAL STAGE OF PULMONARY TUBERCULOSIS TREATMENT USING MOLECULAR-GENETIC METHODS TO TEST SUSCEPTIBILITY TO RIFAMPICIN - A. V. Golovnin; A. L. Khanin; V. I. Golovnin (Туберкулез и болезни лёгких)
The objective of the study: to analyze the frequency and patterns of drug resistance of Mycobacterium tuberculosis (MTB) according to the results of microbiological tests of surgical specimens of the patients who underwent surgery due to tuberculosis, and to compare them with the results of sputum tests done in the pre-operative period. Subjects and methods. The data of surgical specimens from 170 patients operated due to tuberculosis were analyzed. The surgical specimens were sent for histological and microbiological tests (detection of MTB DNA and rifampicin resistance by GeneXpert, culture on solid media with drug sensitivity testing). Results. The molecular genetic testing of surgical specimens by GeneXpert was highly effective for detection of rifampicin resistance; in 97.8% of cases, there was a match with the results of sputum culture with consecutive DST performed before the surgery. Molecular genetic tests of surgical specimens allowed detecting MTB DNA in 66.1% of patients in whom no MTB or MTB DNA was detected in sputum and bronchial washings prior to the surgery, and of them in 28.2% of cases, rifampicin resistance was detected, which was unknown before the surgery. These data allowed prescribing adequate chemotherapy immediately after surgery.